Soil impact on plant hydraulics revealed by leaf rehydration kinetics - Daan C. Piovano; Ibrahim Bourbia; Andrea Carminati; Sara Di Bert; Tim Brodribb (Plant and Soil, 2026)
Background and Aims The hydraulic conductance of the soil is expected to become limiting for plant transpiration in drying soils. Specifically, coarse textured soils are expected to limit transpiration at less negative soil water potential (Ψ soil ). Yet, there is still limited experimental evidence on Ψ soil and relative transpiration rate at which the decline in soil conductance impacts plant water status and the whole soil to plant hydraulic conductance. This gap is related to the lack of accurate and temporally resolved measurements of soil and plant water potential and hydraulic conductance. Methods We combine rehydration techniques and water potential time-series measurements in wheat plants in two contrasting soil textures to measure the relative importance of soil and plant hydraulic conductance on stem water potential and transpiration rate. Results We found that during imposed water stress, a 50% reduction in transpiration rate was concomitant with the soil hydraulic conductance (K soil ) falling below the plant hydraulic conductance (K plant ): K soil declined to 18–56% of K plant in loam and to 7–39% in sand. Conclusions The relative importance of soil and plant hydraulics was texture-specific, with coarse-textured soils imposing greater resistance on soil to leaf water flow at less negative Ψ soil than fine-textured soils. Upon rewetting, the soil–plant hydraulic conductance rapidly reached values it had before the plant was exposed to drying. These results highlight the soil-texture dependency of soil hydraulic properties on plant response to soil drying. The high temporal resolution and non-invasive experimental method is capable to resolve the effect of declining soil hydraulic conductance on the overall soil–plant conductance. Highlight Leaf rehydration kinetics show that soil, not plant, limits water transport during drought—especially in coarse soils where hydraulic conductance drops at less negative water potential.

Stability of tropical forest tree carbon‐water relations in a rainfall exclusion treatment through shifts in effective water uptake depth - Alexandria L. Pivovaroff; Nate G. McDowell; Tayana Barrozo Rodrigues; Tim Brodribb; Lucas A. Cernusak; Brendan Choat; Charlotte Grossiord; Yoko Ishida; Kolby J. Jardine; Susan Laurance; Riley Leff; Weibin Li; et al. (Global Change Biology, 2021)
Increasing severity and frequency of drought is predicted for large portions of the terrestrial biosphere, with major impacts already documented in wet tropical forests. Using a 4‐year rainfall exclusion experiment in the Daintree Rainforest in northeast Australia, we examined canopy tree responses to reduced precipitation and soil water availability by quantifying seasonal changes in plant hydraulic and carbon traits for 11 tree species between control and drought treatments. Even with reduced soil volumetric water content in the upper 1 m of soil in the drought treatment, we found no significant difference between treatments for predawn and midday leaf water potential, photosynthesis, stomatal conductance, foliar stable carbon isotope composition, leaf mass per area, turgor loss point, xylem vessel anatomy, or leaf and stem nonstructural carbohydrates. While empirical measurements of aboveground traits revealed homeostatic maintenance of plant water status and traits in response to reduced soil moisture, modeled belowground dynamics revealed that trees in the drought treatment shifted the depth from which water was acquired to deeper soil layers. These findings reveal that belowground acclimation of tree water uptake depth may buffer tropical rainforests from more severe droughts that may arise in future with climate change.

The maximum height of grasses is determined by roots - Kun‐Fang Cao; Shi‐Jian Yang; Yong‐Jiang Zhang; Tim J. Brodribb (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 666–672 Abstract Grasses such as bamboos can produce upright stems more than 30 m tall, yet the processes that constrain plant height in this important group have never been investigated. Air embolisms form commonly in the water transport system of grasses and we hypothesised that root pressure‐dependent refilling these embolisms should limit the maximum height of grass species to the magnitude of their root pressure. Confirming this hypothesis, we show that in 59 species of bamboo grown in two common gardens, the maximum heights of culms of 67 clones are closely predicted by the maximum measured root pressure overnight. Furthermore, we demonstrate that water transport in these bamboo species is dependent on root pressure to repair hydraulic dysfunction sustained during normal diurnal gas exchange. Our results established the critical importance of root pressure in the tallest grass species and provide a new basis for understanding the limits for plant growth.

Leaf hydraulic vulnerability influences species’ bioclimatic limits in a diverse group of woody angiosperms - Chris J. Blackman; Tim J. Brodribb; Gregory J. Jordan (Oecologia, 2012)

Leaf hydraulic evolution led a surge in leaf photosynthetic capacity during early angiosperm diversification - Tim J. Brodribb; Taylor S. Feild (Ecology Letters, 2010)
Ecology letters (2010) 13: 175–183 Abstract Angiosperm evolution transformed global ecology, and much of this impact derives from the unrivalled vegetative productivity of dominant angiosperm clades. However, the origins of high photosynthetic capacity in angiosperms remain unknown. In this study, we describe the steep trajectory of leaf vein density ( D v ) evolution in angiosperms, and predict that this leaf plumbing innovation enabled a major shift in the capacity of leaves to assimilate CO 2 . Reconstructing leaf vein evolution from an examination of 504 angiosperm species we found a rapid three‐ to fourfold increase in D v occurred during the early evolution of angiosperms. We demonstrate how this major shift in leaf vein architecture potentially allowed the maximum photosynthetic capacity in angiosperms to rise above competing groups 140–100 Ma. Our data suggest that early terrestrial angiosperms produced leaves with low photosynthetic rates, but that subsequent angiosperm success is linked to a surge in photosynthetic capacity during their early diversification.

Stem water transport and freeze-thaw xylem embolism in conifers and angiosperms in a Tasmanian treeline heath - Taylor S. Feild; Tim Brodribb (Oecologia, 2001)